2013
DOI: 10.4236/psych.2013.44056
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Startle Reflex during Brief and Sustained Exposure to Emotional Pictures

Abstract: Previous investigations using pictures to elicit an emotional response have shown that the startle reflex habituates over time due to decreased excitation in the obligatory startle processing pathway, an effect that is independent of emotion modulation aspects of the startle response. However, in some instances, startle magnitude has been selectively potentiated during sustained exposure to passively viewed unpleasant pictures. This study assessed startle modulation during brief, alternating and sustained expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…However, such measures are by and large not indicative of changes in emotional valence [ 19 ] because preferred (pleasant) and nonpreferred (unpleasant) experiences can deliver very similar measures of arousal. The SRM measurement technique, on the other hand, is unique due to its sensitivity to emotional valence (or affect) and has been argued to be even more sensitive to emotional states relative to self-reporting or proxy reporting [ 20 ]. SRM therefore has the potential to deliver a reliable measure of emotional valence (degree of experienced pleasantness) in terms of simple motivational preferences without requiring explicit responses.…”
Section: Methodsmentioning
confidence: 99%
“…However, such measures are by and large not indicative of changes in emotional valence [ 19 ] because preferred (pleasant) and nonpreferred (unpleasant) experiences can deliver very similar measures of arousal. The SRM measurement technique, on the other hand, is unique due to its sensitivity to emotional valence (or affect) and has been argued to be even more sensitive to emotional states relative to self-reporting or proxy reporting [ 20 ]. SRM therefore has the potential to deliver a reliable measure of emotional valence (degree of experienced pleasantness) in terms of simple motivational preferences without requiring explicit responses.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of SRM is to measure the magnitude of eye blinks elicited with an unexpected burst of loud auditory white noise while the startled person is exposed to controlled foreground stimulation with varying affective content [28]. Lang et al [29] showed that the level of eye blink magnitude recorded by the unexpected auditory stimulus correlated with the relative appetitive (resulting in smaller eye blinks) or aversive (larger eye blinks) affective content of the visually presented stimuli.…”
Section: Physiological Effects Of Pornographymentioning
confidence: 99%
“…In contrast to ERPs, startle reflex modulation (SRM) is a relatively new technique in this field which has also been used in emotion research to provide information pertaining to raw affective information processing, e.g., [28]. The purpose of SRM is to measure the magnitude of eye blinks elicited with an unexpected burst of loud auditory white noise while the startled person is exposed to controlled foreground stimulation with varying affective content [28].…”
Section: Physiological Effects Of Pornographymentioning
confidence: 99%
See 1 more Smart Citation
“…Preferences related to urban neighbourhoods were reported to be subject to discrepancies between conscious and non-conscious information processing [4]. Brand attitude can change non-consciously without affecting conscious processing [5][6][7] and emotion pictures are processed differently depending on conscious or non-conscious measures being taken [8,9]. SRM became a highly appreciated tool to quantify raw affective responses in the absence of any awareness and it got introduced to various different disciplines including clinical and industrial areas, even marketing [10][11][12][13][14][15].…”
mentioning
confidence: 99%